Análisis y estandarización de métodos de los procesos del área de soldadura en Fábrica de Cocinas su Ahorro. - Enriquez Jami, Erick Joel (2023)
FÁBRICA DE COCINAS SU AHORRO is mainly dedicated to the manufacturing process of industrial kitchens, which carries out its productive activities without any type of instructions for pre-established or standardized methods, affecting the production rate, the quality of the products and the delivery times. clients, likewise, the microenterprise does not keep the work spaces orderly and clean, on the other hand, the management does not require its operators to constantly use protective equipment. In the welding area, shortcomings have been identified in the execution of activities, since setbacks occur due to the lack of a standardized welding method, as well as lack of training for personnel, misuse of protective equipment, poor decision making. measurements in pieces, and delays due to poor finish in points or welding beads. The present research project focuses on executing a detailed study of sequences carried out during the welding processes, as well as establishing the design of a proposal for standardization of methods that leads to improvement of activities, resulting in an increase in production with better quality and efficiency that meets customer demands, contributing to business, administrative and economic growth. Furthermore, the methodology used is inductive in nature, since it has a direction from the specific to the general, because hypotheses of a possible delay of processes in the welding area were made. On the other hand, calculations of the labor productivity of the workforce were carried out, marking a before and after, acquiring a variation of 29.3% difference in labor performance once the standardization proposal was applied, and obtaining a positive general standard time. of 29 minutes and 4 seconds for the welding activities, demonstrating that the objectives proposed in this research project were satisfactorily met.